Diversification of Tilapia into Frozen Food Products with Yellow Seasoning to Enhance the Activity and Economy - Arinta Kusumawardhani; Dynna Hidayah; Sam Tiara Puspa; Zahrani Putri Desta Sania; Ayu Anisa (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Seventy percent of Indonesia's territory consists of water. Several regions make fish farming a livelihood to optimize this potential. One of them is Ponggok Village, Klaten. Ponggok Village already has superior products made from Nile tilapia fish, but product diversification is needed to expand market segmentation and increase income. By diversifying, products will be more interesting and varied and have a higher selling value. Nile tilapia fish can be converted into frozen food products with yellow spices through village community empowerment program training using the fourth step of the ABCD method, named the Asset Based Community Development method. The first step is to "discover" by finding community groups and identifying the needs, especially the people of Ponggok Village. The second step is to "dream" to create dreams for community groups and overcome the problems in marketing Nile tilapia fish. The third step is "design" that overcome the problem of marketing Nile tilapia fish in Ponggok Village; the P2MD team collaborated with Nile tilapia MSMEs by diversifying Nile tilapia fish products into Bumbu Kuning Frozen Food. The fourth step is "destiny", with the implementation of the collaboration between the P2MD team and the Nile tilapia fish MSMEs of Ponggok Village. At this stage, the P2MD team provides training assistance. Through the ABCD method and the collaboration of the P2MD team with Nile Tilapia fish MSMEs, the result is the diversification of Bumbu Kuning Nile tilapia Frozen Food products, which can last approximately three months, so they can be marketed more widely and increase the income of Ponggok Village Nile tilapia MSMEs. Hopefully, the Bumbu Kuning Nile tilapia Fish Frozen Food Training can increase the activity and economy of the Ponggok Village community.